Effective dose to immune cells combined with platelet-to-lymphocyte ratio predicts lymphopenia and prognosis in unresectable locally advanced non-small cell lung cancer - Yang, Haoting; Ma, Jiachun; Tian, Chen; Bao, Shunshun; Zhang, Jingxin; Wang, Fei; Xu, Ying; Yu, Jinming; Chen, Dawei (Frontiers in Immunology, 2025)
BackgroundIn the management of unresectable locally advanced non-small cell lung cancer (LA-NSCLC), the lack of reliable predictive biomarkers for grade ≥ 3 radiation-induced lymphopenia (RIL3+) and prognosis remains a major challenge. This study aims to investigate whether effective dose to immune cells (EDIC) combined with pre-radiotherapy (RT) peripheral blood inflammatory indicators (PBIIs), especially platelet-to-lymphocyte ratio (PLR), could better predict RIL3+ and prognosis in patients with unresectable LA-NSCLC in the immunotherapy era.MethodsWe enrolled 139 patients with unresectable LA-NSCLC who received chemoradiation and consolidation immunotherapy. Logistic regression was used to identify the predictors of RIL3+. Spearman correlation analyses were used to estimate the correlations between each indicator and absolute lymphocyte count (ALC) nadir. Receiver operating characteristic (ROC) curves were used to determine the predictive performance and optimal cut-off of each indicator. Patients were then divided into low- and high-risk groups based on the above cut-offs. Cox proportional hazards regression was used to determine prognostic factors for progression-free survival (PFS) and overall survival (OS). Survival outcomes were assessed using Kaplan–Meier methods.ResultsLogistic regression showed that both EDIC (P = 0.002) and PLR (P < 0.001) were significantly associated with RIL3+. ROC curves showed the highest predictive power of the PLR among the PBIIs. Spearman correlation analysis showed that both EDIC (P < 0.001) and PLR (P < 0.001) were significantly correlated with ALC nadir. Compared to the model using EDIC (P = 0.026) or PLR (P = 0.021) alone, the combination of EDIC and PLR showed superior predictive performance. The optimal cut-offs of EDIC and PLR were 4.44 Gy and 107.70, respectively. The incidence rates of RIL3+ in the low- and high-risk groups were 44.3% and 90.0%, respectively (P < 0.001). Compared to the high-risk group, patients in the low-risk group had a longer median PFS (P = 0.011) and OS (P = 0.013).ConclusionsIn the immunotherapy era, the combination of EDIC and pre-RT PLR is a predictive biomarker of RIL3+ and prognosis in patients with unresectable LA-NSCLC. Reducing EDIC and considering pre-RT PLR may potentially avoid RIL3+ and improve prognosis.